THE ANALYSIS OF DETERMINANT ON CUSTOMER REPURCHASE BEHAVIOR AT MATAHARI DEPARTMENT STORE MANADO TOWN SQUARE - Wakary, Gizela. C.; Pangemanan, Sifrid S.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2019)
One way to retain customers and make customers buy again is by analyzing what factors affect the customerâ€™s intention to repurchase. Matahari Department Store is the largest retail company in Indonesia engaged in fashion, Matahari Department Store has 151 outlets in more than 60 cities and one online store MatahariStore.com. The purpose of this research was to analyze the factors that influence Customer Repurchase. In the beginning of the research there are twenty factors that are determined as material for testing and research. The methodology of this research is quantitative which used two kinds of factors analysis method both explanatory factor analysis and confirmatory factor analysis. The samples of the research are 100 samples which are the customers of Matahari Department Store Manado Town Square. In the result of the study there is one thirteen factor that eliminated which is Competition, Regulation, Perceived, Promotion, Business Segment, Psychological, Trends, Word of Mouth, Price Lining, Discount, Product Variety, Place and Environment, this factor eliminated because the extraction value of this factor less than 0.5. And suggestions for companies to be able to analyze again what are the factors influence the customers buying interest or how to maintain it.Â Keywords: repurchase behavior, marketing, consumer behavior, brand, trust.